Going against the grain in literary studies: an analysis of boosters, hedges and other rhetorical strategies in The Pilgrimage of Dorothy Richardson by Joanne Winning - Llantada Díaz, María Francisca (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2009)
In The Pilgrimage of Dorothy Richardson (2000), Joanne Winning negotiates her claim to credibility in the world of Richardson’s studies when introducing a theory that goes against the grain. The study of boosters, hedges and other rhetorical strategies in its introduction and afterword will be of key importance to show how Winning conciliates her self-assurance about her proposal with her deference to other researchers. Researchers are able to convince their colleagues if they have full command of rhetorical strategies to present their findings in an acceptable way. Thus, this article will analyse how boosters, hedges and the coexistence of self-mention with impersonalization strategies help Winning create an adequate scholarly identity for herself that guarantees her inclusion in the literary critical scene.